Mainstreaming communication of adaptation to climate change: Some initiatives from Central Africa - Sonwa, D.J.; Mbede, E.; Bele, M.Y.; Abilogo, E.; Ngaunkam, P. (Intellect, 2022)
Despite its low carbon emission, Africa is one of the regions most impacted by the adverse effects of climate change. Because of its impacts on health, infrastructure, settlements, agriculture and food security, and forest ecosystems, climate change is an additional burden to sustainable development in Central Africa. As such, there is an urgent need to transfer lifesaving information about the environment and especially the effects and adaptation to climate change in the region. However, in a region where there is still a relatively high incidence of illiteracy, very localized languages and dialects and remote settlements, communicating information can be a challenge. In addition, communication schools and journalists are insufficiently equipped to respond to this demand. A survey in Cameroon revealed that journalists are faced with some challenges (such as lack of training and lack of resource persons) in covering environment topics, especially those related to forest and climate change adaptation. In order to address these challenges and contribute to the improvement of the journalistic style of reporting topics on forest and climate change adaptation with more scientific knowledge and to create a stronger scientific base of event coverage, pilot capacity-building initiatives were initiated with the specific objectives as follows: (1) training of journalists during workshops; (2) fellowships award for research activities to communication master students; (3) mentoring of senior and junior journalists and (4) open reflection on how to mainstream forests and adaptation to climate change in curricula of communication schools in Central Africa. This last initiative of mainstreaming forests and adaptation to climate change in the school curricula was seen as a possible sustainable way to promote scientific and environmental communication in Central Africa. These activities initiated by CIFOR (Center for International Forestry Research) under the framework of CoFCCA project (Congo Basin Forest and Climate Change Adaptation) were pilot initiatives aiming to inspire others on capacity building and research related to scientific and environmental communication in Central Africa.